2017
DOI: 10.1515/opag-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Agaricus bisporus (button mushroom) and its usages in the biosynthesis of nanoparticles

Abstract: White button mushroom (Agaricus bisporus), Higher Basidiomycota, is a very important nutritional and medicinal species which is used for recycling agrowastes including wheat straw, reed plant wastes, waste paper, oat straw, waste tea leaves, some water plants and others. A. bisporus has many usages in human dietary and pharmaceutical fields due to its composition of essential amino acids, fatty acids, carbohydrates, low calories, crude fibers, trace elements and vitamins. Recently synthesized nanoparticles fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Here, we evaluated the capacity of 7 basidiomycetes species, also known as white-rot fungi, to detoxicate different protein-rich biomasses and combined with lignocellulosic ones from coconut husks (CH) and Acronomia aculeata (macauba cake -MC). The data obtained here showed that although A. subrufescens and L. edodes were able to grow in lignocellulosic wastes, as described by some authors [34,35] who reported growing in composts such as sawdust and wheat straw; these two species were not able to grow in pure JCS and CSC biomasses or combined with CH and MC. The cultivation of A. subrufescens has being described as complex, demanding N supplementation during all growth besides requiring strict environmental controls [36] which, may explain why no growth was achieved in the biomasses tested here.…”
Section: Discussionsupporting
confidence: 58%
“…Here, we evaluated the capacity of 7 basidiomycetes species, also known as white-rot fungi, to detoxicate different protein-rich biomasses and combined with lignocellulosic ones from coconut husks (CH) and Acronomia aculeata (macauba cake -MC). The data obtained here showed that although A. subrufescens and L. edodes were able to grow in lignocellulosic wastes, as described by some authors [34,35] who reported growing in composts such as sawdust and wheat straw; these two species were not able to grow in pure JCS and CSC biomasses or combined with CH and MC. The cultivation of A. subrufescens has being described as complex, demanding N supplementation during all growth besides requiring strict environmental controls [36] which, may explain why no growth was achieved in the biomasses tested here.…”
Section: Discussionsupporting
confidence: 58%
“…Here, we evaluated the capacity of 7 basidiomycetes species, also known as white-rot fungi, to detoxicate different protein-rich biomasses and combined with lignocellulosic ones from coconut husks (CH) and Acronomia aculeata (macauba cake -MC). The data obtained here showed that although A. subrufescens and L. edodes were able to grow in lignocellulosic wastes, as described by some authors [34,35] who reported growing in composts such as sawdust and wheat straw; these two species were not able to grow in pure JCS and CSC biomasses or combined with CH and MC. The cultivation of A. subrufescens has being described as complex, demanding N supplementation during all growth besides requiring strict environmental controls [36] which, may explain why no growth was achieved in the biomasses tested here.…”
Section: Discussionsupporting
confidence: 53%
“…Interest in the cultivation of this mushroom is increasing due to its nutritional and medical properties. It is composed from high contents of amino acids, proteins, carbohydrates, fibers, vitamins, micro and macro elements, and unsaturated fatty acids [13,14]. A. bisporus has anticancer, antioxidant, antihyperlipidemic, antidiabetic, antibacterial, antifungal, and anticandidal activities [11].…”
Section: Introductionmentioning
confidence: 99%